Washout DNA copy number analysis by low-coverage whole genome sequencing for assessment of thyroid FNAs - Wu, Linfeng; Zhou, Yuying; Guan, Yaoyao; Xiao, Rongyao; Cai, Jiaohao; Chen, Weike; Zheng, Mengmeng; Sun, Kaiting; Chen, Chao; Huang, Guanli; Zhang, Xiaogang; Zhai, Lijuan; et al. (Frontiers in Endocrinology, 2022)
Background: Papillary thyroid microcarcinoma (PTMC) is defined as a papillary carcinoma measuring ≤10 mm. The current management of PTMC has become more conservative; however, there are high-risk tumor features that can only be revealed postoperatively. For thyroid cancer, BRAF mutations and somatic copy number variation (CNV) are the most common genetic events. Molecular testing may contribute to clinical decision-making by molecular risk stratification, e.g., predicting lymph node (LN) metastasis. Here, we build a risk stratification model based on molecular profiling of thyroid fine needle aspiration (FNA) washout DNA (wDNA) for the differential diagnosis of thyroid nodules. Methods: Fifty-eight patients were recruited and FNA wDNA samples were analyzed by CNV profiling by low-coverage whole genome sequencing and BRAF mutation by qPCR. FNA pathology was reported according to The Bethesda System for Reporting Thyroid Cytopathology (BSRTC). Ultrasound examination was reported according to the thyroid Imaging Reporting and Data System (TIRADS). Results: In total, 37 (63.8%) patients with TIRADS 4A, 13 (22.4%) 4B, and 8 (13.8%) 4C were recruited after ultrasound examinations. Of these, 24 (41.4%) presented nodules sized ≤5 mm. All patients underwent FNA with wDNA profiling. CNVs were identified in 17 (29.3%) patients. CNVs were frequent in BSRTC score V and VI patients, including 8 (47.1%) score VI patients and 5 (29.4%) score V patients, but not in score III, II, or I patients (0%). BRAF mutation was not significantly correlated with the BSRTC scores. LN metastasis was found more frequently in CNV positive than negative patients (85.7% vs 34.6%, odds ratio = 11.33, P=0.002). In total, three molecular subtypes of thyroid nodules were identified in this study, 1) CNV+, 2) CNV-, BRAF+, and 3) CNV-, BRAF -. For the CNV+ subtype, 10 (83.3%) lesions with LN metastasis were found, including 4 (100%) small lesions (≤5 mm). For the CNV- BRAF+ nodules, LN metastases were only detected in 7 (60.0%) larger nodules (>5 mm). For CNV-, BRAF- tumors, LN metastasis was also only frequently found in larger nodules. Conclusions: It is feasible to identify high-risk LN metastasis thyroid cancer from FNA washout samples preoperatively by wDNA CNVs using low-coverage WGS.